2018
DOI: 10.1007/s10616-018-0195-7
|View full text |Cite
|
Sign up to set email alerts
|

Melilotus indicus extract induces apoptosis in hepatocellular carcinoma cells via a mechanism involving mitochondria-mediated pathways

Abstract: Melilotus indicus, is a traditional medicine used as analgesic and emollient. Although Melilotus indicus extract (MIE) has recently been shown to suppress growth of several tumor cell lines, information regarding its antitumor mechanism is completely unknown. Here, we report the mechanism underlying the effects of MIE on human hepatocellular carcinoma cells, specifically HepG2, and SNU-182 cells. Methanolic MIE impaired the proliferation, and induced cell death in both HepG2 and SNU-182 cells but not in normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…On the contrary, anti-apoptotic molecules such as Bcl-2 can prevent the conformational change and oligomerization of Bax and Bak [33, 34]. Furthermore, induction of apoptosis is correlated with an increase in the ratio of proapoptotic/antiapoptotic Bax/Bcl-2 [35, 36]. Our results showed that nor-wogonin treatment downregulated Bcl-2 protein expression and upregulated Bax protein expression, resulting in an increase in Bax/Bcl-2 ratio, which could be a possible mechanism by which nor-wogonin induced a loss in the Δψm.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, anti-apoptotic molecules such as Bcl-2 can prevent the conformational change and oligomerization of Bax and Bak [33, 34]. Furthermore, induction of apoptosis is correlated with an increase in the ratio of proapoptotic/antiapoptotic Bax/Bcl-2 [35, 36]. Our results showed that nor-wogonin treatment downregulated Bcl-2 protein expression and upregulated Bax protein expression, resulting in an increase in Bax/Bcl-2 ratio, which could be a possible mechanism by which nor-wogonin induced a loss in the Δψm.…”
Section: Discussionmentioning
confidence: 99%
“…Our preceding findings support the idea that in ALD, the major apoptotic signal transduction cascade involves the Bcl‐2 family. Increased Bax and/or decreased Bcl‐2 expression leads to a loss of mitochondrial membrane potential and opening of the mitochondrial permeability transition pores (Abd El‐Hafeez et al., ), which is catastrophic for cells and results in release of cytochrome c into the cytosol. In the cytosol, cytochrome c activates apoptosis by binding and activating the apoptotic protease activating factor 1 (Apaf‐1)–caspase‐9 complex, which forms an apoptosome acts as a processing/activation center for the downstream caspase‐3 (Shahali, Ghanadian, Jafari, & Aghaei, ), leading to poly(ADP‐ribose) polymerase (PARP) cleavage (Gogvadze, Orrenius, & Zhivotovsky, ), and promotes DNA fragmentation, decreases oxygen consumption, and increases ROS, which can ultimately result in the initiation of apoptosis (Li et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the study lacked the characterization of the bioactive compounds to corroborate their anticancer therapeutic approach [31]. Likewise, in the ME of leaves of the species A. macroura Gomes., the active components were not specifically mentioned and their cytotoxic activity against HepG-2 cells (IC 50 = 0.513 mg/mL) was higher compared to other species such as Schinus molle L. (IC 50 = 0.050 mg/mL) [32].…”
Section: Anticancer Activitymentioning
confidence: 94%